2021
DOI: 10.1002/jcp.30189
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GLUT3 promotes metastasis of triple‐negative breast cancer by modulating the inflammatory tumor microenvironment

Abstract: Triple-negative breast cancer (TNBC) exhibits a higher level of glycolytic capacity and are commonly associated with an inflammatory microenvironment, but the regulatory mechanism and metabolic crosstalk between the tumor and tumor microenvironment (TME) are largely unresolved. Here, we show that glucose transporter 3 (GLUT3) is particularly elevated in TNBC and associated with metastatic progression and poor prognosis in breast cancer patients. Expression of GLUT3 is crucial for promoting the epithelial-to-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Reprogramming of glycolysis facilitates the EMT, which also plays crucial roles in cancer stemness, metastasis, and drug resistance [35,36]. Previous studies, including ours, reported that overexpression of glucose transporter 3 (GLUT3) promoted the EMT and invasiveness of glioma, colon, and breast cancer cells [37][38][39]. Additionally, ENO1 and LDHA were reported to promote the EMT and stemness in lung and breast cancer cells [40,41], suggesting that upregulation of glycolytic genes by YBX1 plays a crucial role in promoting tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Reprogramming of glycolysis facilitates the EMT, which also plays crucial roles in cancer stemness, metastasis, and drug resistance [35,36]. Previous studies, including ours, reported that overexpression of glucose transporter 3 (GLUT3) promoted the EMT and invasiveness of glioma, colon, and breast cancer cells [37][38][39]. Additionally, ENO1 and LDHA were reported to promote the EMT and stemness in lung and breast cancer cells [40,41], suggesting that upregulation of glycolytic genes by YBX1 plays a crucial role in promoting tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 80%
“…Aberrant glycolysis is commonly associated with proinflammatory responses and immune evasion in the TME [37,44]. Recent studies showed that YBX1 regulated programmed death ligand 1 (PD-L1) expression to mediate immune escape in prostate cancer [45], and the infiltrating cluster of differentiation 4-positive (CD4+) T cells promoted the growth of renal cell carcinoma via modulating transforming growth factor-β1 (TGFβ1)/YBX1/HIF2α signals [46].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse IL33 shRNAs (TRCN0000173324 and TRCN0000173352) and mouse YAP shRNAs (TRCN0000238432 and TRCN0000238436) in pLKO.puro vectors were purchased from the National RNAi Core Facility (Academia Sinica, Taipei, Taiwan). HEK293T cells were transfected following the manufacturer's instructions, and virus-containing supernatants were collected after 2 d. Cells were incubated with supernatants for 2 d, and then stably selected using puromycin (Tsai et al 2021).…”
Section: Short Hairpin (Sh)rna and Lentiviral Infectionmentioning
confidence: 99%
“… 40 Upregulated GLUT1 and GLUT3 promote glucose uptake, cancer metastasis and growth. 45 , 46 Moreover, GLUT4 is also upregulated in various cancers, leading to elevated glucose uptake and enhanced cancer progression. 47 , 48 Several lncRNAs affect glucose uptake by regulating GLUT expression or distribution.…”
Section: Regulatory Mechanisms Of Lncrnas In Cancer Glycolysismentioning
confidence: 99%